Increasing and Decreasing Development of Integrated Modern Islamic Boarding School (PMT) Prof. Dr. Hamka Batang Anai in 2016–2022 - Seri Indah; Kaksim Kaksim; Refni Yulia; Adi Wiranata (Historia, 2026)
This study aims to examine the rise and fall of Pesantren Modern Terpadu (PMT) Prof. Dr. Hamka, focusing on the temporary relocation of student learning activities from Kecamatan Batang Anai, Kabupaten Padang Pariaman, to Pesantren Modern Terpadu (PMT) Prof. Dr. Hamka II in Kota Padang. The research employs historical methods, including heuristics, source criticism, analysis, and historiography. Data were gathered through interviews with relevant figures, as well as document and literature studies. The findings reveal that the pesantren, established in 1991, experienced significant development before facing a decline marked by a decrease in the number of students, ultimately leading to the relocation of its educational activities. This study provides insights into the internal dynamics of the pesantren in responding to the challenges of social and institutional change.